BUDAYA PEREMPUAN SEBAGAI OBJEK POLITIK (STUDI KASUS ACEH BARAT DAN NAGAN RAYA) - Iis Haryani; Balqis Fahira Ninggrum; Syarah Audia; Nofrizal Nofrizal; Nodi Marefanda (Universitas Teuku Umar, 2018)
The Women are often used as political objects throughout the country to gain advantage in getting voice support to advance as representatives of the people or other political officials. This research is to analyze the culture of women as political object and want to know the factors that cause the influence of women is bigger when compared to men in West Aceh and Nagan Raya district. This research uses qualitative approach with descriptive type. The analysis is done by relying on the findings of data that have been collected and relevant information from the bibliography (secondary data). This study uses the theory of Gabriel A. Almond and Malinowsky theory. The results of the study found that in Aceh Barat District and Nagan Raya District, the perpetrators were always used as political objects in seeking support to gain power based on the parameters of Political Socialization, Political Recruitment, Political Communication and Political Culture. Factors that cause women as a political object are: Money Politic and Poverty, Lack of Political Education, Women as the Majority as well as the Conditions of a Patriarchal Society. Keywords: Aceh Barat dan Nagan Raya, Budaya, Perempuan, Politik.